Edgar Allan Poe - Asselineau, Roger (University of Minnesota pamphlets on American writers ;, 1970)
Edgar Allan Poe - American Writers 89 was first published in 1970. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.